Infrastructure planning the third congress of civil engineers : introductory notes : Harrogate, 17-19 April 1986. (Thomas Telford, 1986)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of third congress of civil engineers held in Harrogate on 17-19 April 1986.
Keywords: Infrastructure (Economics) -- Planning -- Congresses.; Public works -- Planning -- Congresses.; elektronické knihy; electronic books